INFECTIOUS DISEASES AND ANTIMICROBIAL RESISTANCE: CURRENT CLINICAL DEVELOPMENTS AND UPDATE - Herbert, Ernest; Fournier, Dominique (Sanamed, 2024)
Four years into the most virulent disease outbreaks of our generation—where COVID-19 became the most widely discussed infection, claiming millions of lives and leaving countless others suffering from long-term symptoms—host-pathogen interactions has never been more significant.This interplay between hosts and pathogens, alongside evolving risks of emerging infectious diseases, has been exacerbated by the exponential growth of human activities.This review focuses on host-pathogen interactions, the fight against antimicrobial resistance, the current status of antimicrobial usage, and alternative strategies to address this global health crisis.
Keywords: Infectious diseases; host-pathogens interactions; microbial drug resistance; drug design; vaccine development